Possibility of electronic delivery of acts related to the realization of rights and obligations of employees - Antić, Aleksandar; Urdarević, Bojan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The authors in this work will deal with the issues related to the electronic delivery of acts related to the realization of the rights and obligations of employees with an appropriate comparative legal analysis. Acts related to the rights and obligations of employees that appear in the mutual traffic between the employer and the employee are most often rescript by which the employer decides on the rights and obligations of the employee, but also letters that form official communication between the employee and the employer, such as requests, application, letters and similarly. In the Labor Law of the Republic of Serbia, the possibility of electronic delivery of acts which decide on the exercise of the rights and obligations of employees appears as an exception. Having in mind the development of information and communication technologies, as well as the change in the way of work caused by that, and especially during the "coronavirus" pandemic, it is necessary to envisage the possibility of electronic delivery of acts related to official communication between employers and employees in other cases, except those currently provided in the Labor Law of the Republic of Serbia.